Comparative Analysis of The Influence of Bank Financial Performance on Loan Distribution for MSME in Indonesia - Sipayung, Alya Anggreani; Fitanto, Bahtiar (Contemporary Studies in Economic, Finance and Banking, 2025)
This study aims to examine a comparative analysis of the effect of the financial performance of conventional state-owned banks, reflected in the Capital Adequacy Ratio (CAR), Return on Assets (ROA), Non-Performing Loans (NPL), and Loan to Deposit Ratio (LDR), on MSME credit distribution during the periods January 2016-December 2019 and January 2021-December 2024. The analysis was conducted using Multiple Linear Regression. The results for the 2016–2019 period show that, individually, only ROA had a significant effect on MSME credit distribution. Simultaneously, the independent variables did not significantly affect MSME credit distribution. The analysis results for the 2021–2024 period demonstrate that CAR and LDR had no significant effect. On the other hand, ROA and NPL had a significant effect on MSME credit distribution. Simultaneously, all variables had a significant influence on MSME credit distribution. The study results indicate a significant difference in the financial performance of state-owned conventional banks in relation to MSME credit distribution in Indonesia between the 2016–2019 and 2021–2024 periods